Portugal : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation on Portugal highlights that after an extended strong economic expansion, the GDP growth stalled in 2002 and, at 0.5 percent, fell below the euro area average for the first time in almost a decade. The growth slowdown reflected a broad-based decline in domestic demand as households began to adjust to high indebtedness levels and a deteriorating employment outlook. Investment continued to fall amid slowing demand prospects and rising global and domestic uncertainty. The weakness in domestic demand led to a decline of imports.